Augmented Reality and Its Use in Elementary School Education: A Systematic Literature Review - Tarmidzi, Tarmidzi; Andari, Kadek Dewi Wahyuni; Sari, Atikah; Nuryanti, Mira; Arfiyanti, Riskha; Noto, Muchamad Subali (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Learning in elementary schools, in this era of information technology development, should ideally utilize existing technology to enhance students' motivation and interest in learning. Ultimately, this can address learning issues and improve students' understanding and thinking abilities. This study aims to determine augmented reality's contribution and practical implications in elementary school education. This research used a Systematic Literature Review (SLR) with a selection of 29 articles related to the use of augmented reality in elementary school education. The PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method is employed for article searches in this research. The PRISMA method consists of four stages: (1) data search; (2) data screening; (3) data eligibility; (4) identifying similarities and differences from the obtained data. Based on the review results, it is evident that augmented reality positively contributes to various subjects and can be integrated with games and STEM education. Augmented reality also has excellent practical implications in education because it can increase students' motivation, interest, understanding, and critical and creative thinking abilities. Augmented reality is also capable of enhancing students' 21st-century skills.